Spaniards in Mauthausen : representations of a Nazi concentration camp, 1940-2015 - Brenneis, Sara J. (Toronto Iberic, 2018)
"Spaniards in Mauthausen is the first study of the cultural legacy of Spaniards imprisoned and killed during the Second World War in the Nazi concentration camp Mauthausen. By examining narratives about Spanish Mauthausen victims over the past seventy years, author Sara J. Brenneis provides a historical, critical, and chronological analysis of a virtually unknown body of work."--